Application of bio polymer reinforced with natural fiber for car door panel - Hew, Xiao Jun (2016)
Natural fiber reinforced with bio polymer composite has raised great interest in many sectors, especially in automotive industry. The automotive industry is currently transforming to "green" since sustainable development policies tend to broaden with the growing concern for the environment. These bio composites are fully recyclable and biodegradable as they can be completely decomposed at the end of their useful life. They posses low density and satisfactory mechanical properties. In this paper, Quality Function Deployment (QFD) and Analytical Hierarchy Process (AHP) methods were applied in the selection of the most optimum bio composites materials for car door panel. The material selection process was carried out based on product design specifications of the car door panel to meet the customer requirements as well as sustainability factors using the principles of Quality Function Deployment (QFD). Based on literature review, there are five combination of bio polymer matrix reinforced with natural fibers composites were identified as the alternatives materials. A four level of AHP hierarchy structure was constructed which consists of a main goal, five main criteria, seven sub-criteria and five alternative materials. The overall results revealed that poly lactic acid (PLA) reinforced with kenaf fiber is the most appropriate candidate composite material for car door panel based on the highest priority ranking score. Sensitivity analysis was also performed by varying the weight of the main criteria to prove the findings are not dependent on unclear decisions. Furthermore, Finite Element Analysis (FEA) was conducted to further validate the obtained results by determining stress and deformation. From all these analysis, it can be concluded that PLA reinforced kenaf fiber is the best material which can use as the material for car door panel among all the other alternatives materials.